2006
DOI: 10.1371/journal.pone.0000124
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 Up-Regulates TNF-α-Dependent Osteoclastogenesis in Patients Affected by Solid Tumor

Abstract: BackgroundInterleukin-7 (IL-7) is a potent regulator of lymphocyte development, which has also significant effects on bone; in fact it is a potent osteoclastogenic factor. Some human solid tumors produce high IL-7 levels, suggesting a potential IL-7 role on tumor development and progression.MethodologyWe studied 50 male patients affected by solid tumors, and their blood samples were collected at tumor diagnosis. PBMCs were isolated and cultured with/without IL-7 to study its influence on osteoclastogenesis. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 37 publications
4
72
1
Order By: Relevance
“…This result differs from our previously published data on osteotropic tumors, where we demonstrated that IL-7 was high in patients with spontaneous osteoclastogenesis, as it stimulated OC differentiation through RANKL (23). In the present study, in gastric cancer, we did not show the same mechanism since RANKL did not promote osteoclastogenesis.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This result differs from our previously published data on osteotropic tumors, where we demonstrated that IL-7 was high in patients with spontaneous osteoclastogenesis, as it stimulated OC differentiation through RANKL (23). In the present study, in gastric cancer, we did not show the same mechanism since RANKL did not promote osteoclastogenesis.…”
Section: Discussioncontrasting
confidence: 99%
“…In previous studies on bone metastases by solid tumors, we demonstrated a role of IL-7 in promoting osteoclastogenesis (23). Thus, we administered IL-7 serum levels in 31 gastric cancer patients.…”
Section: Serum Level Of Il-7 Rankl and Vegfmentioning
confidence: 97%
“…Primarily, researchers observed increased TNFα production by T cells both in ovariectomized mice [19] and postmenopausal women [2,20] . TNFα enhances OC formation by up-regulating stromal cell production of RANKL and M-CSF and by increasing the responsiveness of OC precursors to RANKL [5,21] . Besides, other studies showed a key role of T cell-produced TNFα in rheumatoid arthritis [3,22] , multiple myeloma [23,6] and bone metastasis [4,5] .…”
Section: Cytokines and Oc Formationmentioning
confidence: 99%
“…Inflammatory disease characterized by systemic and local bone loss is an interesting field with which to explore the relationship between activation of the immune system and bone remodelling. In the last few years, investigators have shed light on this topic and T cells have been recognized as key regulators of osteoclast (OC) and osteoblast (OB) [1] formation and activity in different pathological conditions, such as osteoporosis [2] , rheumatoid arthritis (RA) [3] , bone metastasis [4,5] and periodontitis [6,7] . Estrogen deprivation induces bone loss.…”
Section: Introductionmentioning
confidence: 99%
“…IL-7 plays an important role in immune reconstitution after bone marrow transplantation, 3 it contributes to immunopathology in arthritis 4 and IL-7-producing cancer cells mediate TNF-a-dependent osteoclastogenesis. 5 Overexpression of IL-7 leads to profound defects in B-and T-cell regulation including lymphoma formation 6,7 and IL-7-dependent homing of tumor cells to the skin. The plethora of work with IL-7 in physiology and immune pathology has been performed using the 'canonical' form of IL-7, which spans six exons present in 33 kb of the chromosomal band 8q12-13.…”
Section: Introductionmentioning
confidence: 99%